From waste to reuse: Fenton degradation of anticancer drugs in hospital wastewater using iron mining residue - de M Costa‐Serge, Nayara [UNESP]; Emídio, Elissandro S [UNESP]; Lima, Karla VL [UNESP]; Tonetti, Adriano L; Nogueira, Raquel F Pupo [UNESP] (Wiley, 2025)
Abstract BACKGROUND The heterogeneous photo‐Fenton process demands stable and efficient materials as catalysts to decompose hydrogen peroxide and generate reactive oxygen species to promote the degradation of organic contaminants in wastewater. In this study, the catalytic activity of an iron mining residue (IMR) was investigated for the heterogeneous photo‐Fenton degradation of the anticancer drugs 5‐fluorouracil (5‐FU) and cyclophosphamide (CP) present in hospital wastewater (HW). RESULTS High degradation efficiency was observed for 5‐FU (>99%) and CP (>95%) after 45 min at pH 2.5 using 1 mmol L −1 H 2 O 2 , and 0.3 g L −1 IMR in water. The generation of hydroxyl radical, especially under solar irradiation, indicated the role of the catalyst in generating this oxidizing species, which was confirmed by the drastic decrease of degradation in the presence of tert‐butyl alcohol, and by the transformation products of 5‐FU and CP identified during the photo‐Fenton process. IMR showed stability and maintained >95% removal efficiencies over three reuse cycles with negligible iron leaching (< 1 μmol L −1 ). For HW, the application of a vermifiltration pre‐treatment reduced TOC levels from 129 mg L −1 to 21.9 mg L −1 and turbidity from 64 NTU to 12 NTU, enabling the degradation of >80% of 5‐FU in 90 min under optimized conditions (0.3 g L −1 IMR, 3 mmol L −1 H₂O₂, solar irradiation). CONCLUSION It can be concluded that the IMR presents high stability and efficiency for the degradation of anticancer drugs in real wastewater highlighting its potential as a cost‐effective and sustainable catalyst for the photo‐Fenton treatment process. © 2025 The Author(s). Journal of Chemical Technology and Biotechnology published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry (SCI).